Genomic data from Little blue penguin ( Eudyptula minor minor ). ... - Pan, Hailin; Cole, Theresa; Couto, Alvarina; Bi, Xupeng; Machado, André, M.; Brejova, Brona; Fang, Miaoquan; Albertin, Caroline, B.; Zhou, Chengran; Silva, Filipe; Yang, Zhengtao; Gardner, Paul; et al. (GigaScience Database, 2019)
The New Zealand little blue penguin (also known as fairy penguin, blue penguin, little penguin and koror in Mori) is one of the smallest penguins. It is found on the coastlines of New Zealand and the Chatham Islands. They have a slate-blue plumage. Recent genetic, morphological and behavioral research has demonstrated that the New Zealand little blue penguin is a seperate species to the Australian fairy penguin, however this still remains controversial. Populations have recently declined, and they are considered as Least Concern by the International Union for Conservation of Nature (IUCN), however this assessment still classifies the Australian and New Zealand species as conspecific. The New Zealand little penguin is a Taonga, or treasured possession in Mori culture. We sequenced the genome of an adult Little blue penguin from National Aquarium of New Zealand, New Zealand North Island (provided by Helen Taylor) to a depth of approximately 87x with short reads from a series of libraries with various insert ...